The analysis of 7P marketing mix strategy on powder herbal products and red ginger candy in Batu city home industry - Mas, Nasharuddin; Nanik, Sri (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2017)
This study is to examine the effect of 7P marketing mix strategy on customer satisfaction through purchase decision as mediation variable. The samples are customers of 55 customers of herbal powder and red ginger candy products in Batu home industry. The data is collected by questionnaires. The research result shows that 7P marketing strategy affects on customer satisfaction, both directly and indirectly through purchase decision. The purchase decision also has a positive and significant effect on customer decision of herbal powder and red ginger candy products in Batu home industry.Keywords: Marketing Mix, Powder Herbal Product, Red Ginger Candy.